OP0294 TRANSCRIPTIONAL PROFILING OF RA PATIENTS SYNOVIAL TISSUE REVEALS TARGETS FOR PRECISION MEDICINE. (June 2019) - Mandelin, Arthur; Bian, Shurui; Dominguez, Salina; Ruderman, Eric; Cuda, Carla; Winter, Deborah; Perlman, Harris
Abstract : Background: We were the first in the United States to demonstrate the applicability of performing transcriptional profiling of macrophages cells isolated from ultrasound guided synovial biopsies on RA patients (Mandelin et al, A&R 2018 1 ). While the numbers of macrophages are known to corelate with response to therapy in RA patients, little is known about macrophage heterogeneity or dendritic cell (DC) involvement in disease. Objectives: Here, we performed single cell RNA seq and bulk population RNA-seq on RA synovium and peripheral blood (classical monocytes, non-classical monocytes, and DCs) from RA patients in order to compare their genome-wide transcriptional profile within and across individuals. Methods: We obtained blood samples and ultrasound-guided minimally invasive synovial biopsy tissue from RA patients with active disease. Using Fluorescence-Activated Cell Sorting (FACS), we isolated classical monocytes (MHCII+CD14++CD16-), non-classical monocytes (MHCII+CD14+CD16+), and dendritic cells (MHCII+CD1c+) from blood. After processing synovial tissue for single-cell suspension, we isolated CD45+ cells for single cell RNA seq and macrophages (MHCII+CD14+CD11b+CD206+) and dendritic cells (MHCII+CD1c+) by FACS. We extracted RNA from these cell populations and prepared libraries for RNA-seq. These libraries were sequenced on an Illumina NextSeq 500 and assessed for quality of RNA, sequencing, and gene detection. Results: For each cell population, we assessed the variability of gene expression across patients. We identified 5 different populations of macrophages that differ in their origin, response to methotrexate, differentiation status, and activation status. Additionally, as expected, the bulk population of DCs were highly variable across individuals, which this is likely due to the heterogeneity of subtypes within this population as shown in the single cell RNA seq for macrophages. In circulating monocytes, we observed varying levels of common cytokines and chemokines, such as TNF and CCL1. We also compared gene expression across cell populations to characterize transcriptional signatures that were distinctive to a given cell population. In addition to the genes previously known to be unique to dendritic cells vs. monocytes/macrophages in health, we also identified potential pathogenic factors that varied in their expression across cell types. Finally, to explore the relationship between circulating and tissue cell populations, we asked whether there were pathways that were turned on in the blood prior to extravasation into the synovium. For example, we identified genes that maintained their expression across monocytes and synovial macrophages in RA patients supporting the differentiation of the former into the latter. Conclusion: Together, these results provide a survey of myeloid cells in the blood and synovial tissue of RA patients. We aim to understand how these cells vary across patients and what clinical variables and medication status influence their transcriptional profile across individuals. Our long-term goal is to use these studies to better understand the underlying mechanisms of pathogenesis and response to current treatments of RA as well as to identify potential targets for future therapies. Reference: [1] Mandelin, A.M., 2nd, et al. Transcriptional Profiling of Synovial Macrophages Using Minimally Invasive Ultrasound-Guided Synovial Biopsies in Rheumatoid Arthritis. Arthritis & rheumatology (Hoboken, N.J.) 70, 841-854 (2018). Disclosure of Interests: Arthur Mandelin: None declared, Shurui Bian: None declared, Salina Dominguez: None declared, Eric Ruderman Consultant for: Pfizer Inc., Carla Cuda: None declared, Deborah Winter: None declared, Harris Perlman: None declared